Trends, Persistence, and Volatility in Energy Markets - Atanu Ghoshray (Asian Development Bank (ADB), 2011)
This paper makes a threefold contribution to the underlying dynamic properties and causal effects of energy prices. Firstly, the paper makes a study of the underlying trends to help identify the time series path of nonrenewable energy resources, which can have far reaching consequences for economists and policy makers alike. The analysis is extended to also determine the persistence of oil price shocks. Secondly, the study examines the causal relation between oil prices and the macroeconomy allowing for nonlinear models that have been recently advocated in the literature. Finally, this study describes the relation between oil prices and agricultural commodities. From a policy perspective, these interrelationships of agricultural and oil prices warrant careful consideration in the context of the recent energy crisis, which may very well continue in the future.
hdl:11540/1998
Keywords: 330; Energiemarkt; Energiepreis; Fossile Energie; Zeitreihenanalyse